Modern research on religious influence on human health - Żołnierz, Joanna; Sak, Jarosław (Journal of Education, Health and Sport, 2017)
Introduction: Scientific work on religion and its impact on the mental health of man are already over 100-years history. Despite this fact, research on the relationship of religion with physical health have been taken relatively recently. Aim: The aim of this article is to present the process of the development of scientific research in the social and health sciences on the relationship between religion and health. Selected results of research undertaken since the beginning of the twentieth century will be presented in this article. Brief description of the research: Scientific achievements confirm the positive effect of religion on mental, social and physical health. Religion and Spirituality are important aspects of health and affects the quality of human life. In groups of more religious people can be observed e.g.: a lower level of anxiety, increased stress resistance, reduced risk of diseases of the cardiovascular system and lower chronic disease mortality. Religion also supports the formation of positive health behavior and affects patient satisfaction with the quality of the provided health care. Results: Patients express the need to include issues on spirituality and religion in the healing process. They declare also need to talk about these topics with medical staff. Although the high demand, the level of knowledge and preparation of medical personnel in Poland are still inadequate in this area.